Comparison of POC-CCA with Kato-Katz in Diagnosing Schistosoma mansoni Infection in a Pediatric L-Praziquantel Clinical Trial - Yin, Xiaoyan; N’Goran, Eliézer K.; Ouattara, Mamadou; Aka, NAD.; Diakité, Nana R.; Bassa, Fidèle K.; Kourany-Lefoll, Elly; Tappert, Aliona; Yalkinoglu, Özkan; Huber, Eric; Bezuidenhout, Deon; Bagchus, Wilhelmina M.; et al. (Frontiers in Tropical Diseases, 2021)
Introduction Traditionally Schistosoma mansoni infection is diagnosed by the Kato-Katz method. Thick smears from each stool sample are prepared on slides and eggs are counted microscopically. Commercially available point-of-care circulating cathodic antigen (POC-CCA) cassette tests detect schistosomiasis antigens from urine samples in 20 minutes. POC-CCA results are qualitative or semi-quantitative: signal intensity is an indicator of the amount of worm antigens in the sample. Both methods were used in a phase II trial investigating the efficacy and safety of new pediatric formulations of praziquantel (PZQ) among children ≤6 years (NCT02806232). This secondary analysis evaluated the consistency of results between the Kato-Katz and POC-CCA methods. Methods POC-CCA was used to pre-screen for S. mansoni infection. Children with positive results were tested by the Kato-Katz method, and those with positive Kato-Katz results (>1 egg/1 occurrence) were enrolled. Participants (N=444) were treated with different formulations and doses of PZQ. POC-CCA and Kato-Katz were performed at 2–3 weeks after treatment to evaluate drug efficacy. Cure rate (CR) was defined as the proportion of participants with a negative result per POC-CCA, or no eggs in the stool samples per Kato-Katz. Kappa statistic was used to assess the agreement on cure status, and Spearman correlation between POC-CCA positivity and Kato-Katz egg counts was evaluated. Sensitivity and specificity of POC-CCA were calculated using Kato-Katz as a reference standard. Results CR per POC-CCA, measured 2–3 weeks after treatment, was 52% (95% confidence interval [CI]: 48%, 57%) across all treatment arms except in infants aged 3–12 months. CR per Kato-Katz was 83% (95% CI: 79%, 87%). Kappa statistic was 0.16 (95% CI: 0.09, 0.23), indicating that the agreement was slightly better than by chance. Relative to Kato-Katz, POC-CCA’s sensitivity to detect infection was 70% and specificity was 57%. Spearman correlation coefficient between POC-CCA positivity and Kato-Katz egg counts was 0.26 (95% CI: 0.17, 0.34). Conclusion POC-CCA is sensitive and rapid for diagnosing S. mansoni infection, but its performance and consistency with Kato-Katz requires further investigation among young children.